Fabrication and characterization of pHEMA hydrogel conduit containing GelMA-HaMA IPN for peripheral nerve regeneration - Damla Arslantunali Sahin; Cagdas Devrim Son; Vasif Hasirci (Exploration of BioMat-X)
Aim: Small defects after any injury to the periperal nerves results in self-regeneration. However, for larger defects, suturing or grafting are necessary, which may have limitations. Thus, research on nerve guidence conduits is needed without drawbacks. The aim of the study was to develop hydrogel-based conduits containing interpenetrating network (IPN). Methods: Methacrylated gelatin (GelMA)-methacrylated hyaluronic acid (HaMA) IPN was filled the poly(2-hydroxyethylmethacrylate) (pHEMA) the outer conduit. Schwann cells (SCs) were used on the pHEMA and the distal end of the tube was injected with netrin-1 to support model SH-SY5Y cells. Results: 1H-nuclear magnetic resonance (1H-NMR) showed that methacrylation degrees were 94% ± 2% for GelMA and 60% ± 7% for HaMA. The fraction of HaMA increased the degradation rate; pure HaMA degraded in 3 weeks, while pure GelMA in more than 5 weeks. An increase in the fraction of 2-hydroxyethylmethacrylate (HEMA) from 20% to 56% decreased the porosity and the pore size, significantly. SH-SY5Y cells migrated along the conduit in the presence of netrin-1. NeuN expression was increased in 2 weeks indicating neuronal activity. Conclusions: SH-SY5Y cells produced neurites in the IPN. pHEMA conduit including GelMA-HaMA IPN is a good candidate for peripheral nerve regeneration applications. As future studies, the conduit will be tested in vivo for nerve regeneration.